Self‐reported lactose intolerance in clinic patients with functional gastrointestinal symptoms: prevalence, risk factors, and impact on food choices. Issue 8 (19th June 2015) - Zheng, X.; Chu, H.; Cong, Y.; Deng, Y.; Long, Y.; Zhu, Y.; Pohl, D.; Fried, M.; Dai, N.; Fox, M.
Abstract Background Many patients complain of abdominal symptoms with dairy products; however, clinical and psychosocial factors associated with self‐reported lactose intolerance (SLI) have not been assessed in large studies. In particular, data are lacking from lactase deficient populations. This prospective cohort study assessed the prevalence of, and risk factors for, SLI in Chinese patients attending a gastroenterology clinic. Methods Consecutive patients completed questionnaires to assess digestive health (Rome III), psychological state (HADS), life event stress (LES), food intake, and quality‐of‐life (SF‐8). A representative sample completed genetic studies and hydrogen breath testing (HBT) at the clinically relevant dose of 20 g lactose. Key Results SLI was present in 411/910 (45%) clinic patients with functional abdominal symptoms. The genotype in all subjects was C/C‐13910. A small number of novel SNPs in lactase promoter region were identified, including C/T‐13908 which appeared to confer lactase persistence. Over half of the patients (54%) completed the 20 g lactose HBT with 58% (285/492) reporting typical symptoms. Positive and negative predictive values of SLI for abdominal symptoms during HBT were 60% and 44%, respectively. Psychological state and stress were not associated with SLI in clinic patients. SLI impacted on physical quality‐of‐life and was associated with reduced ingestion of dairy products, legumes, and dried fruit (p ≤ 0.05). Conclusions & Inferences In a lactase deficient population, approximately half of patients attending clinic with functional gastrointestinal symptoms reported intolerance to dairy products; however, SLI did not predict findings on 20 g lactose HBT. Independent of psychosocial factors, SLI impacted on quality‐of‐life and impacted on food choices with restrictions not limited to dairy products.